2020
DOI: 10.1080/00107514.2021.1880075
|View full text |Cite
|
Sign up to set email alerts
|

Testing quantum theory with thought experiments

Abstract: Imagination will often carry us to worlds that never were. But without it we go nowhere.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Alice and Wigner turn out to have descriptions of the same setting which are vastly different from each other. We will not discuss numerous conceptual implications of the original thought experiment here-a review can be found in [21]. However, we would still like to see how we can model this setting in the toy theory (here we will do so in the original epirestricted picture).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Alice and Wigner turn out to have descriptions of the same setting which are vastly different from each other. We will not discuss numerous conceptual implications of the original thought experiment here-a review can be found in [21]. However, we would still like to see how we can model this setting in the toy theory (here we will do so in the original epirestricted picture).…”
Section: 4mentioning
confidence: 99%
“…The contradiction is found for a specific choice of initial state and measurement bases, which are described in appendix C.2. 5 For a pedagogical discussion of the original paradox and the assumptions behind it, we refer to our previous work [23]; for discussions of broader implications for abstract logic and interpretations of quantum theory see for example [5,21,24,25]. The paradox has also been shown to arise in other physical theories, namely box world [7].…”
Section: Example Of Multi-agent Paradoxes: the Frauchiger-renner Scen...mentioning
confidence: 99%
“…Formal quantum experiments In investigations by [2,44], programming languages have served as tools in providing outcomes to thought experiments about physical theories. We envision using (an extension of) QuantumΠ for similar purposes-e.g.…”
Section: Quantum Algorithms: Simon and Grovermentioning
confidence: 99%
“…In the "extended Wigner's friend" thought experiment of FR there are two friends ostensibly making measurements and two outside observers. Here we follow the naming convention and notation of [14], where the friends are named Alice and Bob, and the corresponding outside observers Ursula and Wigner. In the thought experiment, Alice is meant to measure a qubit system R in the computational basis, Bob a qubit system S, also in the computational basis.…”
Section: A Resolution To the Fr Paradoxmentioning
confidence: 99%